Comparison of radiofrequency electromagnetic field exposure levels in different everyday microenvironments in an international context. (May 2018) - Sagar, Sanjay; Adem, Seid M.; Struchen, Benjamin; Loughran, Sarah P.; Brunjes, Michael E.; Arangua, Lisa; Dalvie, Mohamed Aqiel; Croft, Rodney J.; Jerrett, Michael; Moskowitz, Joel M.; Kuo, Tony; Röösli, Martin
Abstract: Background: The aim of this study was to quantify RF-EMF exposure applying a tested protocol of RF-EMF exposure measurements using portable devices with a high sampling rate in different microenvironments of Switzerland, Ethiopia, Nepal, South Africa, Australia and the United States of America. Method: We used portable measurement devices for assessing RF-EMF exposure in 94 outdoor microenvironments and 18 public transport vehicles. The measurements were taken either by walking with a backpack with the devices at the height of the head and a distance of 20–30 cm from the body, or driving a car with the devices mounted on its roof, which was 170–180 cm above the ground. The measurements were taken for about 30 min while walking and about 15–20 min while driving in each microenvironment, with a sampling rate of once every 4 s (ExpoM-RF) and 5 s (EME Spy 201). Results: Mean total RF-EMF exposure in various outdoor microenvironments varied between 0.23 V/m (non-central residential area in Switzerland) and 1.85 V/m (university area in Australia), and across modes of public transport between 0.32 V/m (bus in rural area in Switzerland) and 0.86 V/m (Auto rickshaw in urban area in Nepal). For most outdoor areas the major exposure contribution was from mobile phone base stations. Otherwise broadcasting was dominant. Uplink from mobile phone handsets was generally very small, except in Swiss trains and some Swiss buses. Conclusions: This study demonstrates high RF-EMF variability between the 94 selected microenvironments from all over the world. Exposure levels tended to increase with increasing urbanity. In most microenvironments downlink from mobile phone base stations is the most relevant contributor. Highlights: We measured RF-EMF in 94 matched microenvironments in six countries. We applied a common protocol for direct comparison of RF-EMF. Downlink and broadcasting exposure was most relevant in outdoor microenvironments. Uplink is only relevant in public transport with the highest in Switzerland. Exposure in urban areas tended to be higher.